The Effect Of Transport Protocol Performance On Encrypted Traffic Through Ad Hoc Networks - Andi Gunanta Ginting (Jurnal Mekintek : Jurnal Mekanikal, Energi, Industri, Dan Teknologi, 2021)
The rapid development of communication technology in wireless communication has led to an increase in technologies related to wireless communication. The WLAN (Wireless Local Area Network) network is one example of a network that continues to experience developments in the wireless communication technology. One of the WLAN network configurations is an ad hoc network. Different protocols, data transmission in an ad hoc WLAN will also experience differences in performance. This final project examines the use of three (2) transport protocols, namely TCP and UDP with their use in WLAN with ad hoc networks and the encryption decryption process to determine the percentage comparison of the success of packet delivery. To analyze the comparison of the three transport protocols on an ad hoc network, the Network Simulator 2 (NS-2) application which is integrated into the Ubuntu operating system and algorithms used such as arcfour, rijndael-192 and tripledes is used. The results showed that the percentage of successful data transmission on TCP was greater with an average of 99.318% on the arcfour algorithm, 99.185% on the rijndael-192 algorithm, 99.132% on the tripledes algorithm. While the percentage of success in sending data on UDP is smaller with an average of 70.711% on the arcfour algorithm, 63.971% on the rijndael-192 algorithm, 64.412% on the tripledes algorithm.